Questions of the general psychology in works of Mashkhur Zhusup Kopeyev (The Journal of Psychology and Sociology, 2017)
This article is devoted to the analysis of questions of the general psychology in works of Mashkhur Zhusup Kopeyev. Development of psychological views of Mashkhur Zhusup Kopeyev represents very actual task. Now the Kazakh people and the Kazakh youth need enrichment of the inner world and a reinforcement of patriotic feelings, and studying of views of the outstanding Kazakh poet can introduce in it the contribution.The analysis of a creative heritage of the outstanding Kazakh religious philosopher and great seer Mash khurZhusupKopeyev shows that many questions have been raised by him exclusively deeply, and the ideas stated by the thinker can be estimated quite only today. In essence, Kopeyev has outstripped the time because now we solve those problems with which he grappled and reflected a century ago. Kopeyev’s merit, in our opinion, consists that he helped the person to specify time of his existence, to distinguish itself in crowd of both predecessors, and contemporaries. He sincerely believed that only the philosophy is ca pable to slightly open to us secret of life, to present happiness and in general to carry out an esthetic justification of human existence. The Kazakh thinker, fighting for integrity of the sources, not wishing to submit and be dissolved in new forms of life and thinking in connection with transition to settled life, tried to draw a future trajectory, congenial for Kazakhs. He believed that the philosophy gains national character not in answers – the scientific answer, really, for all people and languages is one and only,– but in the state ment of questions, in selection of these questions.Analyzing various traits of character, Kopeyev wrote: “The clever person is moderate, moderate is steady, patient, patient is without grief”. Though this classification of traits of character is interesting in the psy chological relation, the moderation is excessively absolutized here and carelessness as a positive trait of character is eulogized. Works of the thinker during the Soviet period were in disgrace, were repressed and forbidden, were exposed to violent default and oblivion. But time sorts things out: today Kopeyev’s works are actively studied and published, the 20volume collected works of the poet and philosopher were published in the Pavlodar state university; there is also the Center of Mashkhur studies, where scientists comprehen sively analyze a creative heritage of the great fellow countryman.
Keywords: general psychology; philosophy; religion; Kazakh poetry; happiness.